2014
DOI: 10.5603/kp.a2013.0284
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics, aetiology and occurrence of type 2 acute myocardial infarction

Abstract: Type 2 AMI patients were more often female, and they were more often diagnosed as non-ST-segment elevation MI. The prevalence of classical cardiovascular risk factors in this subgroup of patients was very high. The leading cause of AMI was coronary artery spasm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 18 publications
1
19
0
5
Order By: Relevance
“…90% stenosis in left main coronary artery in this case indicated a strong correlation between the stenosis and the extensive transmural ischemia. It is also reported in another study that extensive transmural ischemia could cause ventricular arrhythmia [1]. All the evidences supported that multimorphologic ventricular tachycardia was correlated with myocardial ischemia.…”
Section: Discussionsupporting
confidence: 64%
“…90% stenosis in left main coronary artery in this case indicated a strong correlation between the stenosis and the extensive transmural ischemia. It is also reported in another study that extensive transmural ischemia could cause ventricular arrhythmia [1]. All the evidences supported that multimorphologic ventricular tachycardia was correlated with myocardial ischemia.…”
Section: Discussionsupporting
confidence: 64%
“…In reality, the diagnosis of type 2 MI as defined by troponin elevation can only be associated with another clinical condition as a pathophysiology is not defined. In two studies in the literature, evidence of significant coronary artery disease (CAD) has been required for making the diagnosis of type 2 MI,35 42 although that is not an obligatory part of the definition that was proposed in the universal definition of MI 21 22. There has been no study to date where all patients had their coronary anatomy defined prior to classification into type 1 or type 2 MI.…”
mentioning
confidence: 99%
“…A key finding of this review is that the clinical characteristics of patients with T2MI, which were similar to those of found by Gupta et al Patients with T2MI were older, more often men, more frequently presented with NSTEMI, and had a higher prevalence of cardiovascular risk factors or comorbidities, such as hypertension, smoking, dyslipidemia, diabetes, obesity, heart failure, impaired renal function, anemia, coronary artery disease, atrial fibrillation, cancer, peripheral artery disease, and chronic obstructive pulmonary disease. In this review, most selected studies revealed that the number of men with T2MI was higher than that of women, while a reduced number of studies found the opposite . For example, Gupta et al described T2MI was more common in females compared with T1MI .…”
Section: Discussionmentioning
confidence: 87%
“…The baseline clinical characteristics and treatment of patients with T2MI are summarized in Table . The mean age of patients with T2MI was over 60 years; most studies revealed that the percentage of male patients ranged from 52.8% to 98.6% in patients with T2MI, but the studies of Szymariski et al, Sandoval et al, and Arora et al found percentages of female patients of 60.3%, 59%, and 51.9%, respectively . The ratio of patients with T2MI presenting with non‐ST segment elevation myocardial infarction (NSTEMI) ranged from 70.1% to 97.5% (mean value: 87.1%); all studies found that patients with T2MI often had previous relevant medical history, but EI‐Haddad et al did not describe medical history findings .…”
Section: Resultsmentioning
confidence: 99%